(untitled) (Research, Society and Development, 2020)
The Civil Construction sector has a significant participation in the brazilian economy, being directly linked to the country’s national development and production. The sector’s participation represented 5.3% of the national economy in recent years, with a strong influence on job creation. In addition to housing policies and infrastructure works, sports mega-events have also boosted the sector’s growth. However, the problems of ineffective management in governmental actions to realise these events have triggered the recent economic crisis and the subsequent retraction of the civil construction sector. The present work aims to analyze the reflexes of the current economic crisis in the Brazilian civil construction market, which started in 2014. Based on the statistical analysis, it was possible to evaluate the sector’s behavior as well as the relationship between the economic and civil construction indicators. The theme is relevant for all those interested in the construction sector seeking truthful and reliable information. The results obtained indicate a strong correlation between Brazil’s GDP and the GDP of Civil Construction, as well as an influence on the unemployment rate. The civil construction sector slowly recovering, in accordance with the country’s economic recovery, being the sector that suffered the most impact from the crisis with a retraction of 32.6% throughout the last six years.